Features of Ecological Competence of Students Living in Conditions of Big City (by the Example of the Students of the Peoples' Friendship University of Russia) - S A Mudrak; A V Gagarin; V V Glebov (Peoples' Friendship University of Russia (RUDN University), 2012)
The features of the ecological competence of students in the conditions of the capital megalopolis are investigated in the submitted article. The ecological competence is considered by the authors as a complex and integrated property of an ecologically focused personality in which there is a structure, components and indicators of the ecological culture. The data of a comparative pilot study of the ecological competence of the students of different faculties which testify to the existence of the qualitative and quantitative distinctions are provided in the work.